The profile of maternal mortality in the municipality of Niterói from 2006 to 2015: a retrospective study (Revista Brasileira Multidisciplinar, 2025)
Maternal death is still a public health problem. The majority of maternal deaths are due to preventable or treatable causes. It is extremely important to understand the factors that increase the risks of this event, and because of this, the present study sought to describe the epidemiological profile and characteristics related to maternal mortality that occurred in the city of Niterói in the period from 2006 to 2015. This is an epidemiological study with a descriptive nature and a quantitative approach, carried out using secondary data from Death Certificates (DO`s). 77 maternal deaths were recorded, predominantly 42.85% were residents of Niterói, 75.32% of the occurrences were in public hospital services, the age group was 30 to 39 years old and 20 to 29 years old (both 40%), 56 % black people (black and brown), 65% were single, 60.88% had a level of education less than or equal to high school, 46.75% worked at home and 49.35% of the causes were other obstetric conditions not classified in other parts (O94-O99). It is concluded that the epidemiological profile of maternal mortality that occurred in the city of Niterói in the period from 2006 to 2015 was higher among women of childbearing age and economically active, black, who did not have a campaneiro, who had a low level of education, who did not have profession and place of occurrence was in hospital environments. The data observed are relevant for surveying the profile of maternal mortality in Niterói, as it will contribute to directing public health actions, specifically improving maternal health care.
Keywords: Maternal mortality; Epidemiology; Collective health